Atrial fibrillation. (August 2022) - Stefil, Maria; Lip, Gregory YH.
Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia, with a high prevalence in elderly individuals. It is associated with increased mortality and morbidity, as a result of stroke, systemic embolism and heart failure. Stroke prevention is central in the management of AF. AF is characterized according to stroke risk, symptom severity, severity of AF burden and substrate severity under a novel 4S-AF scheme. The Atrial fibrillation Better Care (ABC) pathway provides a simple strategy that streamlines integrated management of patients with AF. 'A' stands for avoid stroke. The risk of stroke in AF is related to increasing age and coexistent co-morbidities. All patients with AF should be risk-stratified for stroke and bleeding, with the CHA2 DS2 -VASc and HAS-BLED scores, respectively. Until recently, vitamin K antagonists (VKAs) were the mainstay of antithrombotic therapy, but non-VKA oral anticoagulants are now increasingly preferred. 'B' for better symptom management. The subsequent approach to management of AF is largely patient-centred and symptom-driven. It can be broadly described as 'rhythm control' and 'rate control'. Rate control is usually with β-adrenoceptor blockers or non-dihydropyridine calcium channel blockers. Rhythm control may require antiarrhythmic drugs and/or electrophysiological procedures. 'C' for cardiovascular and co-morbidity risk reduction. Associated co-morbidities such as hypertension, diabetes mellitus, heart failure, cardiac ischaemia and sleep apnoea should be addressed, and lifestyle changes (obesity, alcohol excess, smoking) discussed.